Tabayyun in the Digital Era: A Hadith Analysis of Information Verification from the Perspective of Maqasid as-Syari’ah - Sinna Izzatul Himmah (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
The rapid development of digital technology has transformed the way information is produced, distributed, and consumed by society. While digital media facilitates access to information, it also contributes to the widespread dissemination of hoaxes, misinformation, and disinformation that may threaten social stability and public trust. In this context, the Islamic principle of tabayyun (information verification) becomes increasingly relevant as an ethical framework for evaluating information before accepting or disseminating it. This study aims to analyze the hadiths concerning information verification and examine their relevance from the perspective of maqāṣid al-sharī‘ah in responding to the challenges of the digital era. This research employs a qualitative approach using library research. The primary data consist of hadiths related to information verification, communication ethics, and caution in conveying information, while secondary data are derived from books, scientific articles, and studies on digital communication and maqāṣid al-sharī‘ah. Data were analyzed using content analysis with a normative-contextual approach. The findings reveal that the hadiths on information verification emphasize the values of honesty, caution, responsibility, and critical evaluation of information. From the perspective of maqāṣid al-sharī‘ah, tabayyun contributes to the protection of religion (ḥifẓ al-dīn), intellect (ḥifẓ al-‘aql), life (ḥifẓ al-nafs), and wealth (ḥifẓ al-māl) from the harmful effects of misinformation and digital disinformation. Therefore, tabayyun can be understood not only as an ethical principle of communication but also as an instrument for realizing public welfare and preventing social harm in the contemporary digital environment.